Lithium secondary battery and its usage

JP7641646B2Active Publication Date: 2025-03-07TERAWATT TECH KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022532192
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-06-25
Publication Date
2025-03-07
Estimated Expiration
2040-06-25

AI Technical Summary

Benefits of technology

【0019】 本発明によれば、エネルギー密度が高く、サイクル特性に優れるリチウム2次電池、及びその使用方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641646000003
    Figure 0007641646000003
  • Figure 0007641646000004
    Figure 0007641646000004
  • Figure 0007641646000005
    Figure 0007641646000005
Patent Text Reader

Abstract

The present invention provides: a lithium secondary battery which has high energy density and excellent cycle characteristics; and a method for using this lithium secondary battery. The present invention relates to a lithium secondary battery which is provided with a positive electrode collector, a positive electrode that is formed on at least one surface of the positive electrode collector, while comprising a positive electrode active material, a negative electrode that does not comprise a negative electrode active material, and a separator or solid electrolyte that is arranged between the positive electrode and the negative electrode, wherein the positive electrode contains an Li(Ni, Co, Mn)O2 crystal and / or an Li(Ni, Co, Al)O2 crystal, which has a diffraction peak of the (003) plane having a full width at half maximum of more than 0.00° but not more than 0.10° as determined by X-ray diffractometry, at a content of from 20% by mass to 100% by mass relative to the total amount of the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium secondary battery and a method for using the same. [Background technology]

[0002] In recent years, technology for converting natural energy such as solar or wind power into electrical energy has been attracting attention. Accordingly, various secondary batteries have been developed as electricity storage devices that are highly safe and capable of storing a large amount of electrical energy.

[0003] Among them, secondary batteries that charge and discharge by the movement of metal ions between the positive and negative electrodes are known to exhibit high voltage and high energy density, and a typical example is the lithium ion secondary battery. A typical lithium ion secondary battery is one in which an active material capable of retaining lithium is introduced into the positive and negative electrodes, and charging and discharging are performed by the exchange of lithium ions between the positive and negative active materials. In addition, as a secondary battery that does not use an active material in the negative electrode, a lithium metal secondary battery that retains lithium by depositing lithium metal on the surface of the negative electrode has been developed.

[0004] For example, Patent Document 1 discloses a high-energy density, high-power lithium metal anode secondary battery having a volumetric energy density exceeding 1000 Wh / L and / or a mass energy density exceeding 350 Wh / kg when discharged at room temperature at a rate of at least 1 C. Patent Document 1 discloses the use of an ultra-thin lithium metal anode to realize such a lithium metal anode secondary battery.

[0005] Patent Document 2 discloses a lithium secondary battery including a positive electrode, a negative electrode, a separator and an electrolyte interposed therebetween, in which metal particles are formed on a negative electrode current collector, and are transferred from the positive electrode by charging to form lithium metal on the negative electrode current collector in the negative electrode. Patent Document 2 discloses that such a lithium secondary battery can provide a lithium secondary battery with improved performance and life by solving problems caused by the reactivity of lithium metal and problems that occur during the assembly process. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2019-517722 [Patent Document 2] Special Publication No. 2019-537226 Summary of the Invention [Problem to be solved by the invention]

[0007] However, the present inventors have conducted detailed studies on conventional batteries, including those described in the above patent documents, and have found that at least one of the energy density and cycle characteristics is insufficient.

[0008] For example, a typical secondary battery that charges and discharges by transferring metal ions between a positive electrode active material and a negative electrode active material does not have sufficient energy density. In addition, a lithium metal secondary battery that retains lithium by depositing lithium metal on the surface of the negative electrode as described in the above patent document is prone to forming dendrites on the surface of the negative electrode due to repeated charging and discharging, which makes it prone to short circuits and capacity reduction. As a result, the cycle characteristics are insufficient.

[0009] In addition, in order to suppress the discrete growth of lithium metal precipitation in lithium metal secondary batteries, a method has been developed in which a large physical pressure is applied to the battery to keep the interface between the negative electrode and the separator at a high pressure. However, the application of such high pressure requires a large mechanical mechanism, which increases the weight and volume of the entire battery and reduces the energy density.

[0010] The present invention has been made in consideration of the above problems, and has an object to provide a lithium secondary battery having high energy density and excellent cycle characteristics, and a method for using the same. [Means for solving the problem]

[0011] A lithium secondary battery according to one embodiment of the present invention comprises a positive electrode current collector, a positive electrode formed on at least one surface of the positive electrode current collector and having a positive electrode active material, a negative electrode not having a negative electrode active material, and a separator or a solid electrolyte disposed between the positive electrode and the negative electrode, wherein the positive electrode contains Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 crystals having a full width at half maximum of a diffraction peak of the (003) plane measured by X-ray diffraction measurement of more than 0.00° and not more than 0.10° in an amount of 20 mass % or more and 100 mass % or less with respect to the total amount of the positive electrode active material.

[0012] Such a lithium secondary battery has a high energy density because it is provided with a negative electrode that does not have a negative electrode active material, and lithium metal is deposited on the surface of the negative electrode, and the deposited lithium metal is electrolytically dissolved to perform charging and discharging. In addition, in a lithium secondary battery including such a positive electrode, the response of the positive electrode to charging and discharging is within a moderate range, so that the lithium metal deposited on the negative electrode is not completely dissolved during discharging, and some of the lithium metal remains on the negative electrode even after discharging is completed. The lithium metal remaining on the negative electrode serves as a scaffold for the lithium metal to deposit on the negative electrode during subsequent charging, so that the lithium metal is more likely to deposit uniformly on the negative electrode during charging. Therefore, the growth of dendrite-like lithium metal on the negative electrode is suppressed, and the lithium secondary battery has excellent cycle characteristics.

[0013] The Li(Ni,Co,Mn)O2 is preferably LiNi 1-x-y Co x Mn y O2 (wherein 0.05≦x≦0.20, 0.01≦y≦0.15), and the Li(Ni,Co,Al)O2 is preferably LiNi 1-x-y Co x Al y O2 (where 0.05≦x≦0.20, 0.01≦y≦0.15). According to such an embodiment, the discharge efficiency of the lithium secondary battery can be set within a more appropriate range, and therefore the energy density and cycle characteristics of the lithium secondary battery tend to be further improved.

[0014] The content of the positive electrode active material is preferably 50% by mass or more and 100% by mass or less with respect to the entire positive electrode. According to such an embodiment, the discharge efficiency of the lithium secondary battery can be set within a more appropriate range, and therefore the energy density and cycle characteristics of the lithium secondary battery tend to be further improved.

[0015] The lithium secondary battery is a lithium secondary battery in which lithium metal is deposited on the surface of the negative electrode and the deposited lithium is dissolved to perform charging and discharging. According to such an embodiment, the energy density is further increased.

[0016] The negative electrode is preferably an electrode made of at least one selected from the group consisting of Cu, Ni, Ti, Fe, other metals that do not react with Li, their alloys, and stainless steel (SUS). According to such an embodiment, highly flammable lithium metal is not required during production, which leads to further improved safety and productivity. In addition, such a negative electrode is stable, which further improves the cycle characteristics of the secondary battery.

[0017] In the lithium secondary battery, preferably, no lithium foil is formed on the surface of the negative electrode before the initial charge. According to such an embodiment, there is no need to use highly flammable lithium metal during production, which makes the battery safer and more productive.

[0018] The lithium secondary battery according to one embodiment of the present invention may be used under charging conditions of 4.4V or higher. The positive electrode in the lithium secondary battery according to one embodiment of the present invention contains Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 crystals having a full width at half maximum of the diffraction peak of the (003) plane greater than 0.00° and less than 0.10° as measured by X-ray diffraction, in an amount of 20% by mass or more and 100% by mass or less relative to the total amount of the positive electrode active material, and therefore has higher durability against high voltages than the positive electrode of a typical lithium secondary battery. Therefore, even if the lithium secondary battery according to one embodiment of the present invention is used under charging conditions of 4.4V or higher, charging can be performed without damaging the positive electrode. Furthermore, when the lithium secondary battery is used under charging conditions of 4.4V or higher, the amount of lithium metal remaining on the negative electrode after discharge is further increased, and thus the cycle characteristics tend to be further improved. Effect of the Invention

[0019] According to the present invention, it is possible to provide a lithium secondary battery having high energy density and excellent cycle characteristics, and a method for using the same. [Brief description of the drawings]

[0020] [Figure 1] 1 is a schematic cross-sectional view of a lithium secondary battery according to a first embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view of a lithium secondary battery according to a first embodiment of the present invention; [Diagram 3] FIG. 2 is a schematic cross-sectional view of a lithium secondary battery according to a second embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail with reference to the drawings as necessary. In the drawings, the same elements are given the same reference numerals, and duplicated explanations will be omitted. Furthermore, unless otherwise specified, positional relationships such as up, down, left, and right are based on the positional relationships shown in the drawings. Furthermore, the dimensional ratios of the drawings are not limited to those shown in the drawings.

[0022] [First embodiment] (lithium secondary battery) Fig. 1 is a schematic cross-sectional view of a lithium secondary battery according to the first embodiment. As shown in Fig. 1, the lithium secondary battery 100 according to the first embodiment includes a positive electrode current collector 110, a positive electrode 120 formed on one side of the positive electrode current collector 110 and having a positive electrode active material, a negative electrode 130 not having a negative electrode active material, and a separator 140 disposed between the positive electrode 120 and the negative electrode 130.

[0023] (Negative electrode) The negative electrode 130 does not have a negative electrode active material. In a lithium secondary battery having a negative electrode having a negative electrode active material, it is difficult to increase the energy density due to the presence of the negative electrode active material. On the other hand, the lithium secondary battery 100 of this embodiment has a negative electrode 130 that does not have a negative electrode active material, so such a problem does not occur. That is, the lithium secondary battery 100 of this embodiment has a high energy density because lithium metal is deposited on the surface of the negative electrode 130 and the deposited lithium metal is electrolytically dissolved to perform charging and discharging.

[0024] In this specification, the term "negative electrode active material" refers to a material for holding lithium ions or lithium metal (hereinafter referred to as "carrier metal"), which serves as a charge carrier in a battery, in the negative electrode 130, and may be referred to as a host material for the carrier metal. The mechanism of such holding is not particularly limited, but examples thereof include intercalation, alloying, and occlusion of metal clusters.

[0025] Examples of such negative electrode active materials include, but are not limited to, carbonaceous materials, metal oxides, and metals or alloys. Examples of the carbonaceous materials include, but are not limited to, graphene, graphite, hard carbon, mesoporous carbon, carbon nanotubes, and carbon nanohorns. Examples of the metal oxides include, but are not limited to, titanium oxide compounds, tin oxide compounds, and cobalt oxide compounds. Examples of the metals or alloys include, but are not limited to, silicon, germanium, tin, lead, aluminum, gallium, and alloys containing these metals as long as they can be alloyed with the carrier metal.

[0026] The negative electrode 130 is not particularly limited as long as it does not have a negative electrode active material and can be used as a current collector, and examples thereof include at least one selected from the group consisting of Cu, Ni, Ti, Fe, and other metals that do not react with Li, and alloys thereof, and stainless steel (SUS). When SUS is used for the negative electrode 130, various types of SUS that have been publicly known can be used. The above-mentioned negative electrode materials are used alone or in combination of two or more types. In this specification, the term "metal that does not react with Li" refers to a metal that does not react with lithium ions or lithium metal to form an alloy under the operating conditions of a lithium secondary battery.

[0027] The negative electrode 130 is preferably an electrode that does not contain lithium. According to such an embodiment, highly flammable lithium metal does not need to be used during production, so the lithium secondary battery 100 is even more excellent in safety and productivity. From the same viewpoint and from the viewpoint of improving the stability of the negative electrode 130, the negative electrode 130 is more preferably made of at least one selected from the group consisting of Cu, Ni, and alloys thereof, and stainless steel (SUS). From the same viewpoint, the negative electrode 130 is more preferably made of Cu, Ni, or an alloy thereof, and particularly preferably made of Cu or Ni.

[0028] In this specification, "the negative electrode does not have a negative electrode active material" means that the content of the negative electrode active material in the negative electrode is 10 mass% or less with respect to the entire negative electrode. The content of the negative electrode active material in the negative electrode is preferably 5.0 mass% or less, more preferably 1.0 mass% or less, further preferably 0.1 mass% or less, and particularly preferably 0.0 mass% or less with respect to the entire negative electrode. Incidentally, the fact that the secondary battery 100 has a negative electrode that does not have a negative electrode active material means that the secondary battery 100 is an anode-free secondary battery, a zero anode secondary battery, or an anodeless secondary battery in the commonly used sense.

[0029] In addition, in a typical lithium ion secondary battery, the capacity of the negative electrode active material in the negative electrode is set to be the same as the capacity of the positive electrode. Therefore, when the capacity of the negative electrode active material in the negative electrode 130 is smaller than the capacity of the positive electrode 120, for example, 20% or less, 15% or less, 10% or less, or 5% or less, it also means that the "negative electrode does not have a negative electrode active material."

[0030] The average thickness of the negative electrode 130 is preferably 4 μm or more and 20 μm or less, more preferably 5 μm or more and 18 μm or less, and further preferably 6 μm or more and 15 μm or less. According to such an embodiment, the volume occupied by the negative electrode 130 in the lithium secondary battery 100 is reduced, and therefore the energy density of the secondary battery 100 is further improved.

[0031] (Positive electrode current collector) There are no particular limitations on the positive electrode current collector 110 as long as it is a conductor that does not react with lithium ions in the battery. Examples of such positive electrode current collectors include aluminum.

[0032] (positive electrode) The positive electrode 120 is formed on one side of the positive electrode current collector 110 and has a positive electrode active material. In the lithium secondary battery 100 of this embodiment, the positive electrode 120 contains highly crystalline Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 crystals, more specifically, Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 crystals having a full width at half maximum of the diffraction peak of the (003) plane in X-ray diffraction measurement of more than 0.00° and not more than 0.10°, in an amount of 20% by mass or more and 100% by mass or less with respect to the total amount of the positive electrode active material.

[0033] In this specification, the term "positive electrode active material" refers to a material for holding a carrier metal in a positive electrode of a battery, and may be referred to as a host material for the carrier metal.

[0034] Generally, a positive electrode active material with low crystallinity (polycrystalline) has a better response to charging and discharging than a positive electrode active material with high crystallinity, and can efficiently insert and remove carrier metals. Therefore, in the positive electrode of a typical lithium secondary battery, a polycrystalline positive electrode active material is usually used for the purpose of improving its energy density and cycle characteristics. Therefore, it is expected that it is preferable to use a polycrystalline positive electrode active material even in a lithium secondary battery having a negative electrode that does not have a negative electrode active material. However, contrary to such expectations, the present inventors have found that a lithium secondary battery containing a predetermined ratio of a positive electrode active material with high crystallinity as described above has excellent energy density and cycle characteristics. The following reasons are considered as the cause of this, but the reasons are not limited to these.

[0035] In a lithium secondary battery having a negative electrode without a negative electrode active material, when a polycrystalline positive electrode active material is used, most of the lithium metal deposited on the negative electrode by charging is electrolytically dissolved by discharging due to the efficient insertion and removal of carrier metal by the polycrystalline positive electrode active material, so it is considered that almost no lithium metal remains on the negative electrode at the end of discharge. In such a case, when the battery is charged again, there is almost no scaffolding for lithium metal to deposit on the negative electrode, and it is considered that uniform deposition of lithium metal is difficult. Therefore, in a lithium secondary battery having a negative electrode without a negative electrode active material, when a polycrystalline positive electrode active material is used, the deposition form of lithium metal tends to be non-uniform, resulting in poor cycle characteristics. On the other hand, in a lithium secondary battery including a highly crystalline positive electrode active material at a predetermined ratio, such as the lithium secondary battery 100 of this embodiment, the response of the positive electrode to charge and discharge is within a moderate range, so that even when discharge is completed, a part of the lithium metal deposited on the negative electrode by charging is not electrolytically dissolved, and some lithium metal remains on the negative electrode. In such a case, when the battery is charged again, it is considered that there is a certain amount of scaffolding for lithium metal to deposit on the negative electrode, and uniform lithium metal deposition is easy. Therefore, in a lithium secondary battery having a negative electrode that does not have a negative electrode active material, when a highly crystalline positive electrode active material is used in a predetermined ratio, the lithium metal deposition form is likely to be uniform, and the growth of dendritic lithium metal is suppressed.

[0036] In this specification, "growth of dendritic lithium metal is suppressed" means that the growth of lithium metal in a dendritic shape on the surface of the negative electrode is suppressed. In other words, it means that the lithium metal formed on the surface of the negative electrode by charging and discharging the lithium secondary battery or by repeating the charging and discharging is induced to grow in a non-dendritic shape. Here, "non-dendritic shape" is not particularly limited, but typically means a plate shape, a valley shape, or a hill shape.

[0037] Furthermore, the inventors specifically found that when the positive electrode 120 contains crystals of Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 with a full width at half maximum of the diffraction peak of the (003) plane by X-ray diffraction measurement being more than 0.00° and not more than 0.10°, the energy density and cycle characteristics of the lithium secondary battery 100 are improved.

[0038] Li(Ni,Co,Mn)O2 and Li(Ni,Co,Al)O2 are substances commonly used as positive electrode active materials for lithium ion batteries, and are substances that can take in and release lithium ions from the crystal structure by controlling the potential. Li(Ni,Co,Mn)O2 and Li(Ni,Co,Al)O2 can be represented as LiNi 1-x-y Co x Mn y O2 (where 0.00 < x, y < 1.00, and x + y < 1.00), and LiNi 1-x-y Co x Al y O2 (where 0.00 < x, y < 1.00, and x + y < 1.00), respectively.

[0039] The crystallinity of such Li(Ni,Co,Mn)O2 crystals and Li(Ni,Co,Al)O2 crystals can be estimated by X-ray diffraction measurement, and it is known that the smaller the half-width of the diffraction peak obtained by the measurement, the higher the crystallinity. In addition, in Li(Ni,Co,Mn)O2 crystals and Li(Ni,Co,Al)O2 crystals, the plane with the highest peak intensity is generally the (003) plane. Therefore, in the lithium secondary battery of this embodiment, the Li(Ni,Co,Mn)O2 crystals and Li(Ni,Co,Al)O2 crystals in which the full width at half maximum of the diffraction peak of the (003) plane by X-ray diffraction measurement is more than 0.00° and 0.10° or less have sufficient crystallinity to effectively and reliably achieve the effects of this embodiment described above. The lithium secondary battery of this embodiment obtains high energy density and excellent cycle characteristics by using a positive electrode containing such Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 crystals in a content of 20 mass % or more and 100 mass % or less with respect to the total amount of the positive electrode active material.

[0040] The full width at half maximum of the diffraction peak of the (003) plane can be measured by X-ray diffraction measurement according to a conventionally known method. For example, a crystal powder of Li(Ni,Co,Mn)O2 or Li(Ni,Co,Al)O2 is used as a sample, and an X-ray diffraction spectrum is obtained by powder X-ray diffraction measurement using CuKα radiation, and the spectrum is analyzed. The analysis method may also be performed according to a conventionally known method. More specifically, the measurement may be performed according to the method described in the Examples.

[0041] In addition, the full width at half maximum of the diffraction peak of the (003) plane by X-ray diffraction measurement in Li(Ni,Co,Mn)O2 crystals and Li(Ni,Co,Al)O2 crystals can also be measured by a scanning electron microscope (SEM) or a transmission electron microscope (TEM). For example, electron backscatter diffraction measurement (EBSD) using a SEM or electron diffraction measurement (ED) using a TEM can be performed.

[0042] In the positive electrode 120, the full width at half maximum of the diffraction peak of the (003) plane of the Li(Ni,Co,Mn)O2 crystal and the Li(Ni,Co,Al)O2 crystal by X-ray diffraction measurement is preferably 0.01° or more, more preferably 0.02° or more, and even more preferably 0.03° or more. Moreover, the full width at half maximum is preferably 0.09° or less, more preferably 0.08° or less. When the full width at half maximum is within the above range, the response of the positive electrode to charging and discharging becomes more appropriate, and the cycle characteristics of the lithium secondary battery tend to be more excellent.

[0043] Li(Ni,Co,Mn)O2 crystals and Li(Ni,Co,Al)O2 crystals having a full width at half maximum of the diffraction peak of the (003) plane in X-ray diffraction measurement of more than 0.00° and not more than 0.10° may be synthesized according to a conventionally known method, or commercially available ones may be used.

[0044] In the positive electrode 120, the Li(Ni,Co,Mn)O2 is preferably LiNi 1-x-y Co x Mn y O2 (where 0.05≦x≦0.20, 0.01≦y≦0.15). The x may be 0.07 or more and 0.19 or less, 0.09 or more and 0.18 or less, or 0.10 or more and 0.17 or less. The y may be 0.02 or more, 0.12 or less, or 0.10 or less.

[0045] In the positive electrode 120, the Li(Ni,Co,Al)O2 is preferably LiNi 1-x-y Co x Al y O2 (where 0.05≦x≦0.20, 0.01≦y≦0.15). The x may be 0.07 or more and 0.19 or less, 0.09 or more and 0.18 or less, or 0.10 or more and 0.17 or less. The y may be 0.02 or more, 0.12 or less, or 0.10 or less.

[0046] The positive electrode 120 may contain a positive electrode active material other than Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 crystals having a full width at half maximum of the diffraction peak of the (003) plane greater than 0.00° and less than 0.10° as measured by X-ray diffraction. Such a positive electrode active material is not particularly limited as long as it is generally used in lithium secondary batteries, and a known material can be appropriately selected depending on the application of the lithium secondary battery. The positive electrode 120 may contain Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 crystals having a full width at half maximum of the diffraction peak of the (003) plane greater than 0.10° as measured by X-ray diffraction. Non-limiting examples of the positive electrode active material that the positive electrode 120 may contain include, for example, layered metal oxides. The layered metal oxides are not particularly limited, but include, for example, cobalt oxide-based compounds, manganese oxide-based compounds, and nickel oxide-based compounds. Typical positive electrode active materials are LiCoO2, LiNi x Mn y O2 (x+y=1), and LiNiO2. The above-mentioned positive electrode active materials may be used alone or in combination of two or more.

[0047] The positive electrode 120 contains Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 crystals having a full width at half maximum of a diffraction peak of the (003) plane greater than 0.00° and less than 0.10° as measured by X-ray diffraction, in an amount of 20% by mass to 100% by mass relative to the total amount of the positive electrode active material. In other words, in the positive electrode 120, the total content of the Li(Ni,Co,Mn)O2 crystals and Li(Ni,Co,Al)O2 crystals having a full width at half maximum of a diffraction peak of the (003) plane greater than 0.00° and less than 0.10° as measured by X-ray diffraction is 20% by mass to 100% by mass relative to the total amount of the positive electrode active material. The total content of Li(Ni,Co,Mn)O2 crystals and Li(Ni,Co,Al)O2 crystals, in which the full width at half maximum of the diffraction peak of the (003) plane by X-ray diffraction measurement is more than 0.00° and not more than 0.10°, may be 30 mass% or more, 40 mass% or more, or 50 mass% or more. Note that the higher the total content of the Li(Ni,Co,Mn)O2 crystals and Li(Ni,Co,Al)O2 crystals, the higher the cycle characteristics of the lithium secondary battery tend to be.

[0048] The positive electrode 120 may contain components other than the positive electrode active material. Such components are not particularly limited, but include, for example, known conductive assistants, binders, solid polymer electrolytes, and inorganic solid electrolytes.

[0049] The conductive assistant in the positive electrode 120 is not particularly limited, but examples thereof include carbon black, single-wall carbon nanotubes (SW-CNT), multi-wall carbon nanotubes (MW-CNT), carbon nanofibers, acetylene black, etc. The binder is not particularly limited, but examples thereof include polyvinylidene fluoride, polytetrafluoroethylene, styrene butadiene rubber, acrylic resin, polyimide resin, etc.

[0050] The content of the positive electrode active material in the positive electrode 120 is preferably, for example, 50% by mass or more, may be 60% by mass or more, 70% by mass or more, 80% by mass or more, or may be 90% by mass or more, based on the entire positive electrode 120. The content of the positive electrode active material in the positive electrode 120 may be 100% by mass or less, 99% by mass or less, or 98% by mass or less, based on the entire positive electrode 120. The content of the conductive assistant may be, for example, 0.5% by mass to 30% by mass or less, based on the entire positive electrode 120. The content of the binder may be, for example, 0.5% by mass to 30% by mass or less, based on the entire positive electrode 120. The total content of the solid polymer electrolyte and the inorganic solid electrolyte may be, for example, 0.5% by mass to 30% by mass or less, based on the entire positive electrode 120.

[0051] (Separator) The separator 140 is a member for preventing the battery from short-circuiting by isolating the positive electrode 120 and the negative electrode 130, while ensuring ionic conductivity of lithium ions that serve as charge carriers between the positive electrode 120 and the negative electrode 130, and is made of a material that does not have electronic conductivity and does not react with lithium ions. The separator 140 also plays a role in retaining the electrolyte. The separator 140 is not limited as long as it plays the above role, and is made of, for example, porous polyethylene (PE), polypropylene (PP), or a laminated structure thereof.

[0052] The separator 140 may be coated with a separator coating layer. The separator coating layer may cover both sides of the separator 140, or may cover only one side. The separator coating layer is not particularly limited as long as it is a material that has ion conductivity and does not react with lithium ions, but it is preferable that the separator coating layer is capable of firmly bonding the separator 140 and a layer adjacent to the separator 140. Examples of such a separator coating layer include, but are not particularly limited to, polyvinylidene fluoride (PVDF), a mixture of styrene butadiene rubber and carboxymethyl cellulose (SBR-CMC), polyacrylic acid (PAA), lithium polyacrylate (Li-PAA), polyimide (PI), polyamideimide (PAI), and a binder such as aramid. The separator coating layer may include inorganic particles such as silica, alumina, titania, zirconia, magnesium oxide, magnesium hydroxide, and lithium nitrate added to the binder.

[0053] The average thickness of the separator 140 is preferably 20 μm or less, more preferably 18 μm or less, and even more preferably 15 μm or less. According to such an embodiment, the volume occupied by the separator 140 in the lithium secondary battery 100 is reduced, and the energy density of the lithium secondary battery 100 is further improved. Moreover, the average thickness of the separator 140 is preferably 5 μm or more, more preferably 7 μm or more, and even more preferably 10 μm or more. According to such an embodiment, the positive electrode 120 and the negative electrode 130 can be more reliably isolated from each other, and the battery can be further prevented from being short-circuited.

[0054] (electrolyte) The lithium secondary battery 100 may have an electrolytic solution. The electrolytic solution may be impregnated into the separator 140, or the lithium secondary battery 100 may be filled with the electrolytic solution to form a finished product. The electrolytic solution is a solution containing an electrolyte and a solvent and having ion conductivity, and acts as a conductive path for lithium ions. Therefore, the lithium secondary battery 100 having the electrolytic solution has a further reduced internal resistance and further improved energy density, capacity, and cycle characteristics.

[0055] The electrolyte is not particularly limited as long as it is a salt, and examples thereof include salts of Li, Na, K, Ca, and Mg. A lithium salt is preferably used as the electrolyte. The lithium salt is not particularly limited, and examples thereof include LiI, LiCl, LiBr, LiF, LiBF4, LiPF6, LiAsF6, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2CF3CF3)2, LiB(O2C2H4)2, LiB(O2C2H4)F2, LiB(OCOCF3)4, LiNO3, and Li2SO4. From the viewpoint of further improving the energy density, capacity, and cycle characteristics of the lithium secondary battery 100, the lithium salt is preferably LiN(SO2F)2. The above lithium salts are used alone or in combination of two or more.

[0056] The solvent is not particularly limited, but examples thereof include dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, acetonitrile, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, chloroethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, trifluoromethyl propylene carbonate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, nonafluorobutyl methyl ether, nonafluorobutyl ethyl ether, tetrafluoroethyl tetrafluoropropyl ether, trimethyl phosphate, and triethyl phosphate. The above-mentioned solvents may be used alone or in combination of two or more.

[0057] (Use of lithium secondary batteries) 2 shows one mode of use of the lithium secondary battery of this embodiment. In the lithium secondary battery 100, a positive electrode terminal 220 and a negative electrode terminal 230 for connecting the lithium secondary battery 100 to an external circuit are joined to a positive electrode current collector 110 and a negative electrode 130, respectively. The lithium secondary battery 100 is charged and discharged by connecting the negative electrode terminal 230 to one end of the external circuit and the positive electrode terminal 220 to the other end of the external circuit.

[0058] The lithium secondary battery 100 is charged by applying a voltage between the positive electrode terminal 220 and the negative electrode terminal 230 such that a current flows from the negative electrode terminal 230 through an external circuit to the positive electrode terminal 220. Charging the lithium secondary battery 100 causes deposition of lithium metal at the interface between the negative electrode 130 and the separator 140.

[0059] In the lithium secondary battery 100, a solid electrolyte interface layer (SEI layer) 210 may be formed at the interface between the negative electrode 130 and the separator 140 by initial charging. The SEI layer 210 to be formed is not particularly limited, and may contain, for example, an inorganic compound containing lithium and an organic compound containing lithium. The typical average thickness of the SEI layer is 1 nm or more and 10 μm or less.

[0060] When the SEI layer 210 is formed in the lithium secondary battery 100, the lithium metal that precipitates during charging of the lithium secondary battery 100 may precipitate at the interface between the negative electrode 130 and the SEI layer 210, or may precipitate at the interface between the SEI layer 210 and the separator 140.

[0061] When the positive electrode terminal 220 and the negative electrode terminal 230 are connected to the charged lithium secondary battery 100, the lithium secondary battery 100 is discharged. The lithium metal precipitated at the interface between the negative electrode 130 and the SEI layer 210 and / or the interface between the SEI layer 210 and the separator 140 is electrolytically dissolved.

[0062] In the positive electrode 120 of the lithium secondary battery 100, the crystals of Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2, in which the full width at half maximum of the diffraction peak of the (003) plane by X-ray diffraction measurement is more than 0.00° and less than 0.10°, are contained in an amount of 20% by mass or more and 100% by mass or less with respect to the total amount of the positive electrode active material, so that the response of the positive electrode to charging and discharging is in an appropriate range, and it is considered that the lithium metal generated at at least one of the interface between the negative electrode 130 and the SEI layer 210 and the interface between the SEI layer 210 and the separator 140 is not completely electrolytically dissolved even after the end of discharge, and a part of it remains. Therefore, when the lithium secondary battery 100 is discharged and then charged again, the remaining lithium metal serves as a scaffold for lithium metal deposition, and it is considered that uniform lithium metal deposition is easy. Therefore, it is believed that the lithium secondary battery 100 has excellent cycle characteristics because the growth of dendritic lithium metal is suppressed even when the battery is subjected to repeated charge and discharge cycles.

[0063] A typical lithium secondary battery containing Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 as a positive electrode active material is usually charged only to about 4.2V to 4.3V. This is because in typical lithium secondary batteries, polycrystalline Li(Ni,Co,Mn)O2 and Li(Ni,Co,Al)O2 are often used, and when a high voltage is applied to such polycrystalline Li(Ni,Co,Mn)O2 and Li(Ni,Co,Al)O2, further amorphousization and phase transition (spinelization and cation migration) occur, causing a decrease in the performance of the positive electrode active material and a significant decrease in the cycle characteristics of the battery. On the other hand, the lithium secondary battery 100 of this embodiment uses Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 with high crystallinity, which is unlikely to cause amorphousization or phase transition even when a high voltage is applied, and therefore can maintain excellent cycle characteristics even when charged to a voltage higher than normal.

[0064] Therefore, the lithium secondary battery 100 of this embodiment can be used under charging conditions of 4.4 V or higher. In addition, when the lithium secondary battery 100 is used under charging conditions of 4.4 V or higher, it is considered that the amount of lithium metal remaining after the end of discharge increases because the amount of lithium metal deposited on the negative electrode during charging increases.

[0065] The charging condition for the lithium secondary battery 100 is not particularly limited, and may be within a range of 4.2 V to 4.3 V, or may be 4.4 V or higher. The charging condition for the lithium secondary battery 100 may be 4.7 V or lower, or may be 4.6 V or lower.

[0066] (Lithium secondary battery manufacturing method) The method for manufacturing the lithium secondary battery 100 as shown in FIG. 1 is not particularly limited as long as it is a method capable of manufacturing a lithium secondary battery having the above-mentioned configuration, and examples thereof include the following methods.

[0067] The positive electrode current collector 110 can be obtained by preparing a conductor that does not react with lithium ions in a battery and processing it to an appropriate size. For example, a metal foil (e.g., Al foil) with a thickness of 5 μm to 1 mm can be prepared and punched to a predetermined size.

[0068] The positive electrode 120 may be manufactured, for example, as follows. First, Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 crystals having a full width at half maximum of the diffraction peak of the (003) plane measured by X-ray diffraction measurement that is greater than 0.00° and less than 0.10° are manufactured by a conventionally known manufacturing method or obtained from a commercially available product. When using a commercially available product, it is sufficient to select a product having a full width at half maximum of the diffraction peak of the (003) plane measured by X-ray diffraction measurement that is greater than 0.00° and less than 0.10° by referring to the manufacturer's public information, and after obtaining the product, it is preferable to confirm by X-ray diffraction measurement that the full width at half maximum of the diffraction peak of the (003) plane is greater than 0.00° and less than 0.10°. The obtained Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 crystals may be used alone as a positive electrode active material, or may be mixed with other positive electrode active materials so that the total content of Li(Ni,Co,Mn)O2 crystals, in which the full width at half maximum of the diffraction peak of the (003) plane as measured by X-ray diffraction is more than 0.00° and not more than 0.10°, and Li(Ni,Co,Al)O2 crystals, is 20 mass% or more and 100 mass% or less with respect to the total amount of the positive electrode active material.

[0069] Next, the obtained positive electrode active material, conductive assistant, and binder are mixed to obtain a positive electrode mixture. The compounding ratio may be, for example, 50% by mass or more and 99% by mass or less of the positive electrode active material, 0.5% by mass to 30% by mass or less of the conductive assistant, and 0.5% by mass to 30% by mass or less of the binder, based on the entire positive electrode mixture. The obtained positive electrode mixture is applied to one side of a positive electrode current collector and press molded. The obtained molded body is punched out to a predetermined size by a punching process to obtain a positive electrode 120.

[0070] Next, the separator 140 having the above-mentioned structure is prepared. The separator 140 may be produced by a conventionally known method, or a commercially available product may be used.

[0071] Next, the above-mentioned negative electrode material, for example, a metal foil (for example, electrolytic Cu foil) having a thickness of 1 μm or more and 1 mm or less, is washed with a solvent containing sulfamic acid, punched out to a predetermined size, and then ultrasonically cleaned with ethanol and dried to obtain the negative electrode 130.

[0072] The positive electrode current collector 110, the positive electrode 120, the separator 140, and the negative electrode 130 obtained as above are laminated in this order to obtain a laminate. The obtained laminate is enclosed in a sealed container together with an electrolyte solution to obtain a lithium secondary battery 100. The sealed container is not particularly limited, but examples thereof include a laminate film.

[0073] [Second embodiment] (lithium secondary battery)

[0074] 3 is a schematic cross-sectional view of a lithium secondary battery according to the second embodiment. As shown in FIG. 3, the lithium secondary battery 300 according to the second embodiment includes a positive electrode collector 110, a positive electrode 120 having a positive electrode active material formed on one side of the positive electrode collector 110, a negative electrode 130 having no negative electrode active material, and a solid electrolyte 310 disposed between the positive electrode 120 and the negative electrode 130. The configurations and preferred aspects of the positive electrode collector 110, the positive electrode 120, and the negative electrode 130 are the same as those of the lithium secondary battery 100 according to the first embodiment, except for the points described below, and the lithium secondary battery 300 exhibits the same effects as the lithium secondary battery 100.

[0075] (solid electrolyte) Generally, in batteries with a liquid electrolyte, the physical pressure applied from the electrolyte to the negative electrode surface tends to vary depending on the location due to fluctuations in the liquid. On the other hand, since the lithium secondary battery 300 includes the solid electrolyte 310, the pressure applied from the solid electrolyte 310 to the negative electrode 130 surface becomes more uniform, and the shape of the carrier metal precipitated on the surface of the negative electrode 130 can be made more uniform. That is, according to this embodiment, the carrier metal precipitated on the surface of the negative electrode 130 is further prevented from growing in a dendritic shape, and the cycle characteristics of the lithium secondary battery 300 become more excellent.

[0076] The solid electrolyte 310 is not particularly limited as long as it is generally used in lithium solid secondary batteries, but a known material can be appropriately selected depending on the application of the lithium secondary battery 300 and the type of carrier metal. The solid electrolyte 310 preferably has ionic conductivity and no electronic conductivity. By having the solid electrolyte 310 have ionic conductivity and no electronic conductivity, the internal resistance of the lithium secondary battery 300 is further reduced and short circuits inside the lithium secondary battery 300 can be further suppressed. As a result, the energy density, capacity, and cycle characteristics of the lithium secondary battery 300 are further improved.

[0077] The solid electrolyte 310 is not particularly limited, but examples thereof include those containing a resin and a lithium salt. Examples of such resins are not particularly limited, but examples thereof include resins having an ethylene oxide unit in the main chain and / or side chain, acrylic resins, vinyl resins, ester resins, nylon resins, polysiloxanes, polyphosphazenes, polyvinylidene fluorides, polymethyl methacrylate, polyamides, polyimides, aramids, polylactic acids, polyethylenes, polystyrenes, polyurethanes, polypropylenes, polybutylenes, polyacetals, polysulfones, and polytetrafluoroethylenes. The above-mentioned resins are used alone or in combination of two or more.

[0078] The lithium salt contained in the solid electrolyte 310 is not particularly limited, but examples thereof include LiI, LiCl, LiBr, LiF, LiBF4, LiPF6, LiAsF6, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2CF3CF3)2, LiB(O2C2H4)2, LiB(O2C2H4)F2, LiB(OCOCF3)4, LiNO3, and Li2SO4. The above-mentioned lithium salts may be used alone or in combination of two or more.

[0079] In general, the content ratio of the resin to the lithium salt in the solid electrolyte is determined by the ratio ([Li] / [O]) of the oxygen atoms in the resin to the lithium atoms in the lithium salt. In the solid electrolyte 310, the content ratio of the resin to the lithium salt is adjusted so that the ratio ([Li] / [O]) is preferably 0.02 or more and 0.20 or less, more preferably 0.03 or more and 0.15 or less, and even more preferably 0.04 or more and 0.12 or less.

[0080] The solid electrolyte 310 may contain components other than the resin and lithium salt. Such components are not particularly limited, but include, for example, a solvent and a salt other than the lithium salt. The salt other than the lithium salt is not particularly limited, but includes, for example, salts of Li, Na, K, Ca, and Mg.

[0081] The solvent is not particularly limited, but examples thereof include those exemplified as the electrolyte that the lithium secondary battery 100 may contain.

[0082] The average thickness of the solid electrolyte 310 is preferably 20 μm or less, more preferably 18 μm or less, and further preferably 15 μm or less. According to such an embodiment, the volume occupied by the solid electrolyte 310 in the lithium secondary battery 300 is reduced, and the energy density of the lithium secondary battery 300 is further improved. Also, the average thickness of the solid electrolyte 310 is preferably 5 μm or more, more preferably 7 μm or more, and further preferably 10 μm or more. According to such an embodiment, the positive electrode 120 and the negative electrode 130 can be more reliably isolated from each other, and the battery can be further prevented from being short-circuited.

[0083] In this specification, the term "solid electrolyte" includes gel electrolytes. The gel electrolyte is not particularly limited, but may include, for example, a polymer, an organic solvent, and a lithium salt. The polymer in the gel electrolyte is not particularly limited, but may include, for example, a copolymer of polyethylene and / or polyethylene oxide, polyvinylidene fluoride, and a copolymer of polyvinylidene fluoride and hexafluoropropylene.

[0084] In addition, in FIG. 3, a solid electrolyte interface layer (SEI layer) may be formed on the surface of the negative electrode 130. The SEI layer to be formed is not particularly limited, and may contain, for example, an inorganic compound containing lithium and an organic compound containing lithium. The typical average thickness of the SEI layer is 1 nm or more and 10 μm or less. When the SEI layer is formed in the lithium secondary battery 300, lithium metal precipitated by charging may precipitate at the interface between the negative electrode 130 and the SEI layer, or may precipitate at the interface between the SEI layer and the solid electrolyte 310.

[0085] (Secondary battery manufacturing method) The lithium secondary battery 300 can be manufactured in the same manner as the manufacturing method of the lithium secondary battery 100 according to the first embodiment described above, except that a solid electrolyte is used instead of the separator.

[0086] The method for producing the solid electrolyte 310 is not particularly limited as long as it can obtain the above-mentioned solid electrolyte 310, but may be, for example, as follows. A resin conventionally used in solid electrolytes and a lithium salt (for example, the resin and lithium salt described above as the resin that the solid electrolyte 310 may contain) are dissolved in an organic solvent. The obtained solution is cast onto a molding substrate to a predetermined thickness to obtain the solid electrolyte 310. Here, the compounding ratio of the resin and the lithium salt may be determined by the ratio ([Li] / [O]) of the oxygen atoms of the resin to the lithium atoms of the lithium salt, as described above. The ratio ([Li] / [O]) is, for example, 0.02 or more and 0.20 or less. The organic solvent is not particularly limited, but acetonitrile may be used, for example. The molding substrate is not particularly limited, but PET film or glass substrate may be used, for example.

[0087] The above-described embodiment is an example for explaining the present invention, and is not intended to limit the present invention to only this embodiment. The present invention can be modified in various ways without departing from the gist of the invention.

[0088] For example, in the lithium secondary battery 100 of the first embodiment and the lithium secondary battery 300 of the second embodiment, the positive electrode 120 may be formed on both sides of the positive electrode current collector 110. In this case, the lithium secondary battery includes two positive electrodes 120, two negative electrodes 130 arranged to face each positive electrode 120, and two separators 140 or solid electrolytes 310 arranged between the positive electrodes 120 and the negative electrodes 130. According to such an embodiment, the capacity of the lithium secondary battery can be further improved.

[0089] The lithium secondary battery of the present embodiment may be a lithium solid secondary battery, which does not require the use of an electrolyte, and therefore does not cause the problem of electrolyte leakage, thereby further improving the safety of the battery.

[0090] In the lithium secondary battery of this embodiment, a lithium foil may or may not be formed between the separator or solid electrolyte and the negative electrode before initial charging. In the lithium secondary battery of this embodiment, if a lithium foil is not formed between the separator or solid electrolyte and the negative electrode before initial charging, highly flammable lithium metal is not required during production, resulting in a lithium secondary battery with even greater safety and productivity.

[0091] The lithium secondary battery of this embodiment may have a current collector arranged so as to contact the negative electrode. Such a current collector is not particularly limited, but may be, for example, a current collector that can be used as a negative electrode material. If the lithium secondary battery does not have a negative electrode current collector, the negative electrode itself acts as a current collector.

[0092] In the lithium secondary battery of this embodiment, terminals for connecting to an external circuit may be attached to the positive electrode collector and the negative electrode. For example, a metal terminal (e.g., Al, Ni, etc.) having a thickness of 10 μm to 1 mm may be bonded to one or both of the positive electrode collector and the negative electrode. A conventionally known method may be used as a bonding method, and ultrasonic welding may be used, for example.

[0093] In this specification, "high energy density" or "having a high energy density" means that the capacity per unit total volume or total mass of the battery is high, and is preferably 900 Wh / L or more or 400 Wh / kg or more, and more preferably 1000 Wh / L or more or 430 Wh / kg or more.

[0094] In addition, in this specification, "excellent cycle characteristics" means that the capacity of the battery is reduced at a low rate before and after a number of charge / discharge cycles that can be expected in normal use. In other words, when comparing the initial capacity with the capacity after a number of charge / discharge cycles that can be expected in normal use, the capacity after the charge / discharge cycles is almost not reduced compared to the initial capacity. Here, the "number of times that can be expected in normal use" is, for example, 30 times, 50 times, 100 times, 300 times, 500 times, or 1000 times, depending on the application of the lithium secondary battery. In addition, "the capacity after the charge / discharge cycle is almost not reduced compared to the initial capacity" means, for example, that the capacity after the charge / discharge cycle is 65% or more, 70% or more, 75% or more, 80% or more, 85% or more, or 90% or more compared to the initial capacity, depending on the application of the lithium secondary battery. EXAMPLES

[0095] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0096] [Powder X-ray diffraction measurement] For the Li(Ni,Co,Mn)O2 and Li(Ni,Co,Al)O2 crystals used in the examples and comparative examples, X-ray diffraction measurements were performed as follows to determine the full width at half maximum of the diffraction peak of the (003) plane in each crystal.

[0097] First, the powder of the positive electrode active material was filled into the frame of a glass sample plate, and the surface of the powder was smoothed with a glass plate. Then, each sample was measured using a powder X-ray diffractometer "X'Pert-PRO" (manufactured by Philips (PANalytical)) under the following conditions. Radiation source: CuKα, X-ray output: 45 kV, 40 mA, scanning range: 10°≦2θ≦60°, sampling interval: 0.0040° / step, scan step time: 15.24 s, divergence slit (opening angle): 0.25°, focus-DS distance: 100.00 mm.

[0098] Next, the diffraction peaks due to Kα2 radiation were removed and the diffraction peaks were smoothed using the powder X-ray diffraction pattern analysis software attached to the X-ray diffractometer, and the full width at half maximum of the diffraction peaks assigned to the (003) plane was then determined.

[0099] [Example 1] LiNi 0.85 Co 0.12 Mn 0.03 Li(Ni,Co,Al)O2 powder was purchased and used as the positive electrode active material. The full width at half maximum of the diffraction peak of the (003) plane in X-ray diffraction measurement (hereinafter, "full width at half maximum of the diffraction peak of the (003) plane in X-ray diffraction measurement" is also simply referred to as "half width") was 0.03°.

[0100] Next, a 12 μm Al foil was prepared as a positive electrode current collector. Then, a mixture of 96 parts by mass of a positive electrode active material, 2 parts by mass of carbon black as a conductive assistant, and 2 parts by mass of polyvinylidene fluoride (PVDF) as a binder was applied to one side of the positive electrode current collector and press molded. The obtained molded body was punched out to a size of 4.0 cm × 4.0 cm by punching processing to obtain a molded body with a positive electrode formed on one side of the positive electrode current collector.

[0101] Next, a 10 μm electrolytic Cu foil was washed with a solvent containing sulfamic acid, and then punched out to a size of 4.5 cm×4.5 cm. The foil was then ultrasonically cleaned with ethanol and dried to obtain a negative electrode.

[0102] A separator measuring 5.0 cm×5.0 cm was prepared, which was made of a 12 μm polyethylene microporous membrane coated on both sides with 2 μm polyvinylidene fluoride (PVDF).

[0103] As an electrolyte, a solution of 4M LiN(SO2F)2 (hereinafter also referred to as "LFSI") in dimethoxyethane (hereinafter also referred to as "DME") was prepared.

[0104] The positive electrode current collector, positive electrode, separator, and negative electrode obtained as above were laminated in this order to obtain a laminate. Furthermore, a 100 μm Al terminal and a 100 μm Ni terminal were joined to the positive electrode current collector and the negative electrode, respectively, by ultrasonic welding, and then inserted into a laminate exterior body. Next, the electrolyte obtained as above was injected into the exterior body. The exterior body was sealed to obtain a lithium secondary battery.

[0105] [Example 2] As the positive electrode active material, LiNi 0.85 Co 0.12 Mn 0.03 A lithium secondary battery was obtained in the same manner as in Example 1, except that O2 (half width: 0.08°) was used.

[0106] [Example 3] As the positive electrode active material, LiNi 0.85 Co 0.12 Mn 0.03 O2 (half width: 0.08°) 50 mass parts and LiNi 0.85 Co 0.12 Mn 0.03 A lithium secondary battery was obtained in the same manner as in Example 1, except that a mixture with 50 parts by mass of O2 (half width: 0.12°) was used.

[0107] [Example 4] As the positive electrode active material, LiNi 0.85 Co 0.12 Mn 0.03 O2 (half width: 0.08°) 20 mass parts, LiNi 0.85 Co 0.12 Mn 0.03 A lithium secondary battery was obtained in the same manner as in Example 1, except that a mixture with 80 parts by mass of O2 (half width: 0.12°) was used.

[0108] [Example 5] As the positive electrode active material, LiNi 0.85 Co 0.12 Mn 0.03 O2 (half width: 0.08°) 50 mass parts and LiNi 0.80 Co 0.15 Al 0.05A lithium secondary battery was obtained in the same manner as in Example 1, except that a mixture with 50 parts by mass of O2 (half width: 0.12°) was used.

[0109] [Example 6] As the positive electrode active material, LiNi 0.80 Co 0.15 Al 0.05 O2 (half width: 0.08°) 50 mass parts and LiNi 0.85 Co 0.12 Mn 0.03 A lithium secondary battery was obtained in the same manner as in Example 1, except that a mixture with 50 parts by mass of O2 (half width: 0.12°) was used.

[0110] [Comparative Example 1] As the positive electrode active material, LiNi 0.85 Co 0.12 Mn 0.03 A lithium secondary battery was obtained in the same manner as in Example 1, except that O2 (half width: 0.12°) was used.

[0111] [Comparative Example 2] As the positive electrode active material, LiNi 0.85 Co 0.12 Mn 0.03 O2 (half width: 0.08°) 10 mass parts, LiNi 0.85 Co 0.12 Mn 0.03 A lithium secondary battery was obtained in the same manner as in Example 1, except that a mixture with 90 parts by mass of O2 (half width: 0.12°) was used.

[0112] [Evaluation of energy density and cycle characteristics] The secondary batteries produced in each of the Examples and Comparative Examples were charged and discharged 50 times in the manner described below to evaluate the cycle characteristics.

[0113] In the first cycle, the secondary battery was charged at 3.2 mA until the voltage reached 4.2 V (hereinafter referred to as "initial charge"), and then discharged at 3.2 mA until the voltage reached 3.0 V (hereinafter referred to as "initial discharge"). In the second to 50th cycles, the battery was charged at 16 mA until the voltage reached 4.2 V, and then discharged at 32 mA until the voltage reached 3.0 V. The temperature was kept at 25° C. in all cycles.

[0114] For each example, the ratio (initial discharge capacity / initial charge capacity) of the amount of electricity flowing in the initial discharge (initial discharge capacity) to the amount of electricity flowing in the initial charge (initial charge capacity) was calculated. The ratio (initial discharge capacity / initial charge capacity) is shown in Table 1 as the initial charge / discharge efficiency (%). The ratio (50th cycle capacity / 2nd cycle capacity) of the capacity obtained from the 50th cycle discharge (50th cycle capacity) to the capacity obtained from the 2nd cycle discharge (2nd cycle capacity) was calculated. The ratio (50th cycle capacity / 2nd cycle capacity) is shown as the capacity retention rate (%) in Table 1. The initial charge capacity was 100 mAh in all examples.

[0115] [Table 1]

[0116] From Table 1, it was found that Examples 1 to 6, which contain 20 mass % or more of Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2 with a half width of more than 0.00° and not more than 0.10° relative to the entire positive electrode active material, have a high capacity retention rate and excellent cycle characteristics compared to Comparative Examples 1 to 2, which do not contain Li(Ni,Co,Mn)O2 and / or Li(Ni,Co,Al)O2. Also, from Table 1, it is found that Examples 1 to 6 have low initial charge / discharge efficiency compared to Comparative Examples 1 to 2. This result suggests that the factor of the excellent cycle characteristics of Examples 1 to 6, which contain a predetermined proportion of highly crystalline positive electrode active material, is that a certain amount of lithium metal remains on the negative electrode even after discharge is completed, promoting uniform deposition of lithium metal.

[0117] [Effects of charging conditions] The secondary batteries prepared in Example 2 and Comparative Example 1 were charged and discharged 50 times under the following different conditions (cycle condition 1 and cycle condition 2) to examine the effect of the charging conditions on the cycle characteristics of the secondary batteries.

[0118] (Cycle condition 1) In the first cycle, the secondary battery was charged at 3.2 mA until the voltage reached 4.2 V (hereinafter referred to as "initial charge"), and then discharged at 3.2 mA until the voltage reached 3.0 V (hereinafter referred to as "initial discharge"). In the second to 50th cycles, the battery was charged at 16 mA until the voltage reached 4.2 V, and then discharged at 32 mA until the voltage reached 3.0 V. The temperature was kept at 25° C. in all cycles. (Cycle condition 2) In the first cycle, the secondary battery was charged at 3.2 mA until the voltage reached 4.4 V (hereinafter referred to as "initial charge"), and then discharged at 3.2 mA until the voltage reached 3.0 V (hereinafter referred to as "initial discharge"). In the second to 50th cycles, the secondary battery was charged at 16 mA until the voltage reached 4.4 V, and then discharged at 32 mA until the voltage reached 3.0 V. The temperature was kept at 25° C. in all cycles.

[0119] For each measurement, the initial charge / discharge efficiency (%) and the capacity retention rate (%) were determined in the same manner as above. The results are shown in Table 2.

[0120] [Table 2]

[0121] From Table 2, it can be seen that in both Example 2 and Comparative Example 1, when charging and discharging were repeated under cycle condition 2, the initial charge and discharge efficiency was low compared to cycle condition 1. This suggests that the proportion of lithium metal remaining after the end of discharge was increased by charging under high voltage conditions. On the other hand, the capacity retention rate was higher under cycle condition 2 in Example 2, and higher under cycle condition 1 in Comparative Example 1. This is because, although the proportion of lithium metal remaining after the end of discharge was increased by charging under high voltage conditions, in Comparative Example 1, the deterioration of the performance of the positive electrode active material due to the application of a high voltage to a positive electrode active material with low crystallinity was significant, and it is considered that the cycle characteristics were generally deteriorated. On the other hand, in Example 2, the deterioration of the performance of the positive electrode active material due to the application of a high voltage to the positive electrode active material hardly occurred, and it is considered that the cycle characteristics were improved. [Industrial Applicability]

[0122] INDUSTRIAL APPLICABILITY The lithium secondary battery of the present invention has high energy density and excellent cycle characteristics, and therefore has industrial applicability as an electricity storage device for various applications. [Explanation of symbols]

[0123] 100, 300... lithium secondary battery, 110... positive electrode current collector, 120... positive electrode, 130... negative electrode, 140... separator, 210... solid electrolyte interface layer, 220... positive electrode terminal, 230... negative electrode terminal, 310... solid electrolyte.

Claims

1. a positive electrode current collector; a positive electrode formed on at least one surface of the positive electrode current collector and having a positive electrode active material; a negative electrode having no negative electrode active material and not containing lithium metal before initial charging; and a separator or a solid electrolyte disposed between the positive electrode and the negative electrode; the positive electrode contains LiNi1-xyCoxMnyO2 (wherein 0.05≦x≦0.20, 0.01≦y≦0.15) and / or LiNi1-xyCoxAlyO2 (wherein 0.05≦x≦0.20, 0.01≦y≦0.15) crystals having a full width at half maximum of a diffraction peak of a (003) plane of 0.03° or more and 0.08° or less as measured by X-ray diffraction, in an amount of 20% by mass or more and 100% by mass or less based on the total amount of the positive electrode active material; Lithium secondary battery.

2. 2. The lithium secondary battery according to claim 1, wherein the content of the positive electrode active material is 50% by mass or more and 100% by mass or less with respect to the entire positive electrode.

3. 3. The lithium secondary battery according to claim 1, wherein the lithium secondary battery is a lithium secondary battery in which lithium metal is deposited on the surface of the negative electrode and the deposited lithium is dissolved, thereby performing charging and discharging.

4. The lithium secondary battery according to any one of claims 1 to 3, wherein the negative electrode is an electrode made of at least one selected from the group consisting of Cu, Ni, Ti, Fe, and alloys thereof, and stainless steel (SUS).

5. A method for using the lithium secondary battery according to any one of claims 1 to 4 under charging conditions of 4.4 V or higher.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery and its manufacturing method

    JP2002237293A

  • Electrochemical active material for positive electrodes of electrochemical lithium storage battery

    JP2005150093A

  • Positive electrode active material, positive electrode and lithium battery having the same, and method of manufacturing positive electrode active material

    JP2014132572A

  • Lithium secondary battery with lithium metal formed on the positive electrode and its manufacturing method

    JP2019505971A

  • High energy density, high power density, high capacity, and room temperature compatible "anode-free" secondary battery

    JP2019517722A